Design of a Novel Video-Assisted Tube Over Tube Rigid Bronchoscope for the Removal of Foreign Bodies from the Bronchi Following Aspiration - McEwan, Sarah Ann (Department of Human Biology, 2023)
Foreign body aspiration (FBA) is a prevalent occurrence in the paediatric population. FBA is when a foreign body (FB) is inhaled accidentally into the airways. The location of the FB may differ according to each patient, but in most cases, the FB is found in the right bronchial tree. FBA symptoms are often misdiagnosed, resulting in late discovery of the obstruction. There is an increase in difficulty to remove a FB, dependent on how long it remains within the airway. This poses a greater risk to the patient, fatality or other serious long-term complications. Currently, FBs are removed using a bronchoscope in conjunction with a pair of forceps. The two types of bronchoscopes used currently are the flexible and rigid bronchoscopes. The rigid scope is preferred for FB removal due to better control and clear visuals of the air way and an array of forceps ends. The costly flexible scope is more difficult to use and is used in cases where radiological findings of a FB are inconclusive. During insertion of the scope, no ventilation is supplied to the patient, posing a high risk of hypoxia. Both instruments require considerable skill and extensive training, limiting the procedure applicability. The difficulty experienced when handling the current instruments and the high risk of hypoxia are motivations for a product redesign. Therefore, this study aims to design and develop a novel video-assisted tube-over-tube rigid bronchoscope to remove foreign bodies from the airways following aspiration, whilst providing constant ventilation and visualisation of the airway. The redesign compromises of several subsystems: the rigid bronchoscope (and attached camera), ventilation connector tube and an uncuffed endotracheal tube (ETT). These subsystems were designed to ensure constant ventilation throughout the insertion of the bronchoscope, whilst providing real-time imaging of the airways. The design incorporated a guiding mechanism to increase the usability further. A testing protocol was performed on a Laerdal airway management trainer using the designed device, named the ‘Re-Aspire' device and its competitor, the Karl Storz rigid bronchoscope. The testing participants were a group of anaesthesiologists who have had prior training in bronchoscopy, but do not practise the procedure. A common FB was placed inside the airway of the trainer, and both scopes were used to retrieve it. The facilitator timed the procedure and observed the participants. Post testing, each participant was interviewed about the functionality of each device and completed a system usability scale. A total of 34 attempts of FB removal was recorded for the rigid bronchoscope compared to 14 attempts for the Re-Aspire device. As hypothesised, the estimated average hypoxic time was more than double for the rigid bronchoscope compared to that of the Re-Aspire device. According to the system usability scale, the Re-Aspire device resulted in a higher average system usability score. These results demonstrated that the Re Aspire device has a higher perceived ease of use and system satisfaction according to the user's perspective. Therefore, achieving all the stated testing hypotheses. However, the design of the device can be improved to increase the usability and efficacy further.